Extracorporeal cardiopulmonary resuscitation for refractory cardiac arrest: A multicentre experience. (15th March 2017) - Dennis, Mark; McCanny, Peter; D'Souza, Mario; Forrest, Paul; Burns, Brian; Lowe, David A; Gattas, David; Scott, Sean; Bannon, Paul; Granger, Emily; Pye, Roger; Totaro, Richard; et al.
Abstract: Aim: To describe the ECPR experience of two Australian ECMO centres, with regards to survival and neurological outcome, their predictors and complications. Methods: Retrospective observational study of prospectively collected data on all patients who underwent extracorporeal cardiopulmonary resuscitation (ECPR) at two academic ECMO referral centres in Sydney, Australia. Measurements and main results: Thirty-seven patients underwent ECPR, 25 (68%) were for in-hospital cardiac arrests. Median age was 54 (IQR 47–58), 27 (73%) were male. Initial rhythm was ventricular fibrillation or pulseless ventricular tachycardia in 20 patients (54%), pulseless electrical activity ( n = 14, 38%), and asystole ( n = 3, 8%). 27 (73%) arrests were witnessed and 30 (81%) patients received bystander CPR. Median time from arrest to initiation of ECMO flow was 45 min (IQR 30–70), and the median time on ECMO was 3 days (IQR 1–6). Angiography was performed in 54% of patients, and 27% required subsequent coronary intervention (stenting or balloon angioplasty 24%). A total of 13 patients (35%) survived to hospital discharge (IHCA 33% vs. OHCA 37%). All survivors were discharged with favourable neurological outcome (Cerebral Performance Category 1 or 2). Pre-ECMO lactate level was predictive of mortality OR 1.35 (1.06–1.73, p = 0.016). Conclusions: In selected patients with refractory cardiac arrest, ECPR may provide temporary support as a bridge to intervention or recovery. We report favourable survival and neurological outcomes in one third of patients and pre-ECMO lactate levels predictive of mortality. Further studies are required to determine optimum selection criteria for ECPR.